Decko kojem se zurilo . The Boy Who Rushed - Cakic-Veselic, Biljana (Factum, 2001)
Duration: 00:53:00 An intimate story about a filmmaker searching for her brother gone missing in 1991 during the recent war in Croatia. The director’s brother, along with many other young soldiers, mysteriously disappeared in Vukovar. While searching for him, the director filmed the events and people she encountered. The film begins with a rather moving confession by the filmmaker about her psychological state, and about her family and native country, which were drawn into the nightmare of the war. In a quite humorous manner, she speaks about the history of Croatia in the previous century and refers to missing soldiers who represented every generation in her family. In a way, it is a "sequel" to her grandmother's story: her husband was killed in World War II, but all her life she's been waiting for him.